JARIMAH TA'JIR MENURUT PERSPEKTIF HUKUM PIDANA ISLAM - Erly Sulistiyawati; Siti Rahmah; Lahmudinur (PT. Pustaka Andil Lestari, 2025)
This study discusses jarimah ta'jīr as a form of criminal offense in Islamic law whose sanctions are not explicitly determined in the Qur'an and Hadith, but are left to the authorities or judges through their respective ijtihad based on the principle of maslahah. The research method used is qualitative with a literature approach, through analysis of primary and secondary sources of Islamic law. The results of the study show that jarimah ta'jīr has high flexibility so that it can accommodate various forms of contemporary crimes such as cybercrime, corruption, drugs, human trafficking, and copyright infringement. The main purpose of applying ta'jīr sanctions is not only repressive but also preventive, educational, and socially corrective, in line with maqāṣid al-syarī'ah in protecting religion, life, intellect, property, and offspring. Thus, jarimah ta'jīr plays an important role in maintaining the relevance, justice, and dynamics of Islamic law in the modern era, while also serving as an adaptive instrument that bridges Sharia values with current global legal challenges and ensures the proportional and sustainable protection of individual and community rights.